Graphene on metallic foils. (2nd December 2016) - Machac, Petr
This work is focused on a simple method of graphene preparation. The method is based on thermal annealing of a carbon/metal structure, where cobalt and nickel were the tested metals. The technological process is based on an optimization of parameters of annealing (temperature and duration) and on a thickness of carbon layer. A multilayered graphene was prepared; for its preparation, annealing temperature within the range of 600–800°C was sufficient.